2008
DOI: 10.1099/mic.0.2007/012427-0
|View full text |Cite
|
Sign up to set email alerts
|

The role of the Serratia marcescens SdeAB multidrug efflux pump and TolC homologue in fluoroquinolone resistance studied via gene-knockout mutagenesis

Abstract: Serratia marcescens is a prominent opportunistic nosocomial pathogen resistant to several classes of antibiotics. The major mechanism for fluoroquinolone resistance in various Gram-negative pathogens is active efflux. Our group previously identified SdeAB, a resistance-nodulation-cell division (RND) efflux pump complex, and a TolC-like outer-membrane protein (HasF), which together mediate energy-dependent fluoroquinolone efflux. In addition, a regulatory protein-encoding gene in the upstream region of sdeAB wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…2, 63 Additional resistance can develop through a variety of mechanisms, including overexpression of AmpC β-lactamase, acquisition of plasmids encoding extended-spectrum β-lactamases (ESBLs), carbapenemases, or efflux pumps, and modifications to target proteins. 2, 41, 63, 64 …”
Section: Treatmentmentioning
confidence: 99%
“…2, 63 Additional resistance can develop through a variety of mechanisms, including overexpression of AmpC β-lactamase, acquisition of plasmids encoding extended-spectrum β-lactamases (ESBLs), carbapenemases, or efflux pumps, and modifications to target proteins. 2, 41, 63, 64 …”
Section: Treatmentmentioning
confidence: 99%
“…Cosmid cloning of the genes responsible for this phenotype identified sdeA and sdeB, which confer resistance to fluoroquinolones, chloramphenicol, sodium dodecyl sulfate (SDS), and ethidium (320). SdeAB's function is dependent on the TolC-like OM protein HasF, and sdeB inactivation increases the susceptibility to fluoroquinolones and other drugs listed above (321). Exposure to a biocide (cetylpyridinium chloride) led to a mutational upregulation of SdeAB and thus antibiotic resistance (322).…”
Section: Serratia Marcescensmentioning
confidence: 99%
“…Exposure to a biocide (cetylpyridinium chloride) led to a mutational upregulation of SdeAB and thus antibiotic resistance (322). SdeAB expression is controlled by a BadM-type repressor, SdeS (323), and a putative MarA-like regulator, SdeR (321). Another RND system (SdeCDE) requires two paired pump genes, sdeDE, but their deletion did not seem to affect the MICs of common antibiotics (320).The RND pump SdeXY produces resistance to fluoroquinolones as well as many substrates of AcrB (16).…”
Section: Serratia Marcescensmentioning
confidence: 99%
“…[5,7,17] It has been previously shown that fl uoroquinolones are the major class of antibiotics extruded by the SdeAB pump. [6,15] In the present study, of the 20 isolates that overexpressed sdeB, 40% were completely resistant to fl uoroquinolones, whereas 77% were resistant to cefoxitin and only 3% were resistant to ceftriaxone and ceftazidime, confi rming that fl uoroquinolones are major substrates for this pump. The reason for high frequency of resistance to cefoxitin is the presence of a wide variety of ß-lactamases, such as AmpC, that are intrinsically present in Serratia spp.…”
Section: Discussionmentioning
confidence: 48%
“…This could possibly be due to mutations in sdeR, the transcriptional regulator of sdeB, leading to constitutive overexpression of the drug effl ux pump, or in hasF, the gene encoding the transmembrane channel, resulting in a non-functional outer membrane component. [6,[18][19][20] One limitation of this study was that we measured the expression of sdeB, but expression does not always correlate with function. If the overexpressed effl ux pump components are mutated, they become nonfunctional, and hence there will not be an equivalent increase in resistance.…”
Section: Discussionmentioning
confidence: 99%